Marjoe - Kernochan, Sarah; Smith, Howard; Lynch, Ed; Myers, David; Pearce, Richard (New Video, 2006)
The Academy Award-winning "Marjoe" is the ferocious and extraordinary chronicle of a firebrand evangelical preacher who wholeheartedly and humorously exposed himself as a fraud. An evangelist prodigy at the age of four, the film captures an adult Marjoe as he recounts how he discovered the seductions of the 60s counterculture and dropped out of preaching, only to return later, using his swaggering bravado, to woo Pentecostal audiences out of their offerings. Directors Howard Smith and Sarah Kernochan follow Marjoe as he embarks on his "farewell to faith tour," revealing the secrets of religious hucksterism. A fiery baptism is the cynical waters of faith healing and evangelical fervor, "Marjoe" is a fascinating profile of a man who went from hellfire to hellraising. [Cover]